Theological Reconstruction in China: Ecumenical Accompaniment in the Self-Theologizing Effort in Theological Education - Wilson, H. S. (International review of mission, 2009)
In 2007 Protestants in China celebrated the 200th anniversary of their journey of faith. The continuing concern of Chinese Christian theological educators is to rejuvenate Christianity in China by critically adapting to the contemporary socialist order and the best religio-cultural tradition of Chinese society. Chinese Christians have been challenged by the socialist order of society particularly because of the political and social changes that have taken place in China since the establishment of the People's Republic of China in 1949 and the changes brought about within Chinese society. With the end of the Cultural Revolution (1966–1976) and the change of political atmosphere in 1978 there has been once again an opening for public Christian activities within the confines of certain state regulations. This change has provided scope for pursuing the reconstruction in China of Christianity initiated in the 1950s under the Three Self Patriotic Movement (TSPM). Besides the revival of TSPM, the Chinese leaders have set up another instrument, the China Christian Council (CCC) especially to cater to the surging pastoral and congregational needs. This article briefly surveys the development of the vision of reconstructing Christianity through “theological reconstruction” and the need for ecumenical accompaniment.